Combined transmastoid/middle fossa approach for a petrous bone cholesteatoma: A case report and literature review. Issue 1 (31st December 2021) - Miyazato, Kiyotaka; Hokama, Yohei; Nagamine, Hideki; Ganaha, Akira; Suzuki, Mikio; Ishiuchi, Shogo
Abstract: We report the case of a 14-year-old girl with petrous bone cholesteatoma resected through a combined approach from the middle cranial fossa and mastoid process. A favorable outcome can be achieved when applying the transmastoid approach to a cholesteatoma by incorporating the middle fossa approach to preserve inner ear function. We emphasize the utility of integrated three-dimensional image reconstruction as a surgical strategy to determine beneficial routes for facial and inner ear function and accomplishment of radical resection. Visualization by an integrated image of irregular tumor infiltration within the petrous bone facilitates information sharing for better cooperation between surgeons in otolaryngeal and neurosurgical fields.